Changes in the audiometric patterns in presbycusis with ongoing medical upgradation - Sugandha Sharma; Girja Thakur; Arvinpreet Kour; Ajaydeep Singh (Apollo Medicine)
Background: Presbycusis or age-related hearing loss. Nowadays, age-related hearing impairment is recognized as a disorder with environmental and genetic factors, use of ototoxic medication, hypertension with increasing age, i.e., longevity of life the burden of presbycusis is increasing. Aims: This study aims to identify patterns based on audiometric data collected from a sample with a clinical indication of presbycusis and to quantify hearing loss at the time of presentation. Materials and Methods: One hundred and forty-five participants were studied, and tuning fork tests, pure-tone audiometry, and speech audiometry were performed. Conclusion: It concluded that hearing loss increased with increasing age and speech discrimination scores decreased with increasing age. The hearing loss associated with presbycusis seen in the elderly was essentially symmetrical. The most common audiogram configuration seen in the study of presbycusis was the Flat type, followed by the high-frequency gently sloping and high-frequency steeply sloping types.